O.J. Simpson - århundrets straffesak i USA. Noen refleksjoner fra TV-stolen - Ståle Eskeland (Nordisk Tidsskrift for Kriminalvidenskab)
The author examines the evidence in the famous O.J. Simpson murder case where Simpson was acquitted. His conclusion is that the prosecution did prove beyond a reasonable doubt that Simpson was guilty. The author discusses some implications of the fact that Simpson was acquitted for reasons not related to the evidence in the case. He argues that it might be justified to acquit for other reasons than lack of evidence in cases where the political system is unable to solve severe conflicts in society or between individuals. In cases of unjustifiable violence, acquittals on other grounds than lack of evidence undermines the jury institution.